Induction of linalool as a pharmaceutical and medicinal metabolite via cell suspension culture of cumin (Cuminum cyminum L.) - Kazemi, N; Kahrizi, D; Mansouri, M; Karim, H; Vaziri, S; Zargooshi, J; Khanahmadi, M; Shokrinia, M; Mohammadi, N (Cellular and Molecular Biology, 2016)
Cumin is an important medicinal plant in Iran. Plant cell suspension culture is a method for the production of medicinal and secondary metabolites. The linalool is a plant secondary metabolite that has been recognized as a neuroprotective agent. The purpose of this study was to evaluate the effects of salicylic acid elicitor on induction of linalool in cell suspension culture of cumin. For this purpose, the cumin seeds were prepared, to obtain sterile seedling, were disinfected with sodium hypochlorite and alcohol, and were cultured on MS basal medium. This research was conducted in two separate experiments including callus induction and suspension cultures. Leaf explants were prepared from sterile seedlings and used to produce callus on MS medium supplemented with 1 mg/l NAA and 0.5 mg/l BAP. In order to establish suspension culture, the appropriate calli were transferred to liquid medium. Then cell cultures were treated with elicitors. The effects of elicitor on the production of linalool secondary metabolite and cell viability were assessed by GC-Mass and tetrazolium test respectively. For this purpose, the salicylic acid (at concentrations of 0, 1, 2, 4 and 8 mg/l) was used. The experimental design was a completely randomized design with five treatments and three replications. The results of cell culture and GC-Mass analysis showed that salicylic acid had significant effects on the linalool production (<0.01). At all concentrations of salicylic acid, viability of the cells in suspension culture experiments was lower than control. Increasing the elicitor concentrations lead to reduction in cell survival. In conclusion it is possible to produce linalool as a secondary metabolite and pharmaceutical agent in cell culture of cumin. It is necessary to determine the best combination of medium and elicitor.